Soft skills characteristics for social workers towards social well-being of society - Shaffie, Fuziah (2014)
Social workers play an important role in maintaining and promoting social well-being of society.Social workers must be competence with their helping skills and also need to be guided to acquire relevant soft skills. Hence, social workers need to have soft skills in order to become competent professionally and socially. This paper discusses conceptualizations of the soft skills within the current perspective, based on an exploratory study recently carried out.A social work expert was asked to describe the experiences of, and viewpoints on, soft skills as part of the professional socialization of social workers to become professionally and socially competent. It is important to raise awareness of soft skills competencies among Malaysian social workers to help them in assessing themselves, and identify where and how they could actively seek to improve themselves as social workers within the context of their workplaces.Embedding the soft skills competencies into their career as social workers is assumed as one of the effective and efficient method of achieving both professional and social competence.The propose soft skills, perhaps, provide early ideas and initiatives which can serve as guideline when facilitating and guiding future qualified social workers in Malaysia.